(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The problem under examination is the magnetic loss of polycrystalline ferrites. Their total loss include: hysteresis, eddy current and anomalous (AN) or excess ones. The mentioned first two losses more or less adequately are covered by modified Steinmetz equation whereas AN loss is less well understood. Conceptually this loss is defined by the components of complex permeability spectra of ferrites which as a rule are experimentally obtained. Large body of these experimental spectra shows a great variety of forms and specific features. This variety is the main reason why there still is not adequate analytic presentation of AN loss. It is shown in the research that important progress is possible to achieve in analytic presentation of AN loss on the basis of realistic account of microstructure of polycrystalline ferrites and dividing the variety of all samples into subgroups according to their actual structure.